Soft tissue sarcoma: clinical recognition and approach to the loneliest cancer - Sujan Shakya; Erandathie Lasanda Banneyake; Sumita Cholekho; Janith Singh; Xiang Zhou (Exploration of Musculoskeletal Diseases)
Soft tissue sarcoma (STS) is a rare malignancy with a high incidence. Early diagnosis can reduce the rate of amputations and increase survival, however, this is typically delayed. The diagnosis and treatment of smaller lesions have a better prognosis; nonetheless, patients present to physicians when the soft tissue mass is large with obvious signs of red flags. In addition, the symptoms of this disease are highly non-specific and overlap greatly with benign conditions, resulting in a lack of clinical suspicion and low awareness among practitioners and the general public. Thusly, it is entitled as “the loneliest cancer”. This can make an accurate diagnosis difficult, with a great proportion of misdiagnoses leading subsequent inadvertent to incomplete STS excision, affecting the overall prognosis of the disease and devastating consequences in the disease process. A timely and precise diagnosis is essential because half of people with STS progress toward quietly aggressive illness. The purpose of this review is to raise awareness of STSs so that early recognition, accurate work-up, overview of conventional treatment plans, and appropriate referral to a tumor center can be achieved, avoiding whoop situations, and improving patient outcomes. In addition, insight into the advances in immunotherapy, nanotechnology, and artificial intelligence (AI) can lead to STS diagnosis and treatment prognosis.